Brand equity and corporate responsibility : a review of brand valuation methods - Pakseresht, Ashkan (SLU/Dept. of Economics, 2010)
During the last decades, brand equity has been a priority topic for both practitioners and academics. In accordance with the structural changes in the economic settings caused by the so-called "new economy", corporations being confronted with a shift on perceived business value structure from tangible assets to intangibles. On the other hand firms increasingly are adopting more responsible behaviour towards their societies. In this context, one critical question is to understand how corporate conduct may affect brand equity. The purpose of this study was to find how brand equity (BE) measurement methods embrace corporate responsibility (CR), based on a literature review.